EVALUASI PROGRAM PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE (P2DBD) - Herlina Susmaneli; Marni Yuliastri; Ulfa Khaira Auzar (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Dengue hemorrhagic fever is a disease severe health problems. Based on the Pekanbaru city health office profile, in 2017 the highest dengue mortality cases were at the puskesmas lima puluh cities in Pekanbaru with a mortality rate of 3.4%, The purpose of this study is generally to obtain information about the implementation of monitoring and evaluation of DHF control programs, with variable periodic larvae, epidemiological investigations, counseling and fogging. The type of research used is descriptive qualitative. With the number of informants 5. From the results of this study there are successes in monitoring of mosquito larvae that are in accordance with standard operating procedures, and there are several programs that have not been monitored, namely epidemiological investigation programs lack of coordination and slow case reports, less scheduled counseling, monitoring is only carried out for fogging officers for fogging only from the health department and seen from the results of evaluation of periodic larvae checks that meet national standards of 95% evaluation of epidemiological investigations that are not in accordance with the number of dengue cases, evaluation of counseling seen from the number of DHF counseling a year conducted 9 times, fogging evaluation which was only done 1 cycle so that the success of fogging was not standardized. Keywords: DHF control program, evaluation